Resin composition, molded article thereof, and method for producing resin composition

JP7644647B2Active Publication Date: 2025-03-12TEIJIN LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021064628
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-03-12
Estimated Expiration
2041-04-06

AI Technical Summary

Benefits of technology

【0032】 本発明の樹脂組成物は、優れた強度を維持しつつ、優れた熱伝導性および電気絶縁性を有することからセンサー、LEDランプ、コネクター、小型スイッチ、コイルボビン、コンデンサー、バリコンケース、光ピックアップ、発振子、各種端子板、変成器、プラグ、プリント基板、チューナー、スピーカー、マイクロフォン、ヘッドフォン、小型モーター、磁気ヘッドベース、パワーモジュール、半導体、液晶、FDDキャリッジ、FDDシャーシ、ハードディスクドライブ部品(ハードディスクドライブハブ、アクチュエーター、ハードディスク基板など)、DVD部品(光ピックアップなど)、モーターブラッシュホルダー、パラボラアンテナ、コンピューター関連部品などに代表される電子部品;VTR部品、テレビ部品、アイロン、ヘアードライヤー、炊飯器部品、電子レンジ部品、音響部品、オーディオ·レーザーディスク(登録商標)·コンパクトディスクなどの音声機器部品、照明部品、冷蔵庫部品、エアコン部品、タイプライター部品、ワードプロセッサー部品などに代表される家庭、事務電気製品部品;オフィスコンピューター関連部品、電話器関連部品、ファクシミリ関連部品、複写機関連部品、洗浄用治具、モーター部品、ライター、タイプライターなどに代表される機械関連部品;顕微鏡、双眼鏡、カメラ、時計などに代表される光学機器、精密機械関連部品;ランプリフレクター、ランプハウジング、センターコンソールパネル、ディフレクター部品、カーナビケーション部品、オートモバイルコンピューター部品などの車両用部品などの各種用途にも適用できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644647000001
    Figure 0007644647000001
Patent Text Reader

Abstract

To provide a resin composition that has excellent thermally conductive and electrically insulative properties while retaining high strength.SOLUTION: A resin composition contains, relative to 100 pts.wt. of (A) polyarylene sulfide resin (A component), (B) graphite (B component) 5-50 pts.wt., (C) talc (C component) 5-80 pts.wt. and (D) glass fiber (D component) 5-80 pts.wt. The C component has a particle size of less than 10 μm by laser diffraction.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition comprising a polyarylene sulfide resin, graphite, talc, and glass fibers, which has excellent thermal conductivity and electrical insulation properties while maintaining excellent strength, a molded article thereof, and a method for producing the resin composition. [Background technology]

[0002] Polyarylene sulfide resin is an engineering plastic with excellent chemical resistance, heat resistance, and mechanical properties. For this reason, polyarylene sulfide resin is widely used in electrical and electronic applications, vehicles, aircraft, housing, and other applications, taking advantage of its excellent properties. In recent years, power consumption has increased with the high integration of LSIs, and heat generation can cause electronic components to malfunction or even break, which has become a problem. Therefore, heat sinks have been installed as a heat dissipation measure to dissipate the generated heat. Traditionally, ceramics, which have high heat dissipation and electrical insulation properties, were generally used for heat sinks, but ceramics need to be cut one by one, which is time-consuming to process, and this has led to cost issues. Therefore, from the perspective of moldability, attempts have been made to increase thermal conductivity by blending heat-dissipating fillers into thermoplastic resins, including polyarylene sulfide resins. Attempts to improve the thermal conductivity of polyarylene sulfide resins have been proposed, for example, a resin composition in which alumina and an inorganic filler are mixed with polyarylene sulfide resin to increase thermal conductivity (Patent Document 1) and a resin composition in which alumina, glass fiber, and talc are mixed with polyarylene sulfide resin to increase thermal conductivity (Patent Document 2). However, the thermal conductivity is not sufficient, and there is also an issue of reduced physical properties due to high filler loading. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-256147 A [Patent Document 2] JP 2013-75996 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a resin composition that has excellent thermal conductivity and electrical insulation while maintaining excellent strength. [Means for solving the problem]

[0005] As a result of extensive research, the inventors discovered that a resin composition comprising polyarylene sulfide resin, graphite, talc and glass fiber is a resin composition that maintains excellent strength while exhibiting excellent thermal conductivity and electrical insulation properties, and thus arrived at the present invention.

[0006] Specifically, the above-mentioned object is achieved by a resin composition containing 100 parts by weight of (A) polyarylene sulfide resin (component A), 5 to 50 parts by weight of (B) graphite (component B), 5 to 80 parts by weight of (C) talc (component C), and 5 to 80 parts by weight of (D) glass fiber (component D), wherein the particle diameter of component C measured by laser diffraction method is less than 10 μm.

[0007] The present invention will be described in detail below.

[0008] (Component A: polyarylene sulfide resin) As the polyarylene sulfide resin used as component A in the present invention, any resin may be used so long as it belongs to the category called polyarylene sulfide resin.

[0009] The polyarylene sulfide resin may be composed of, for example, a p-phenylene sulfide unit, an m-phenylene sulfide unit, an o-phenylene sulfide unit, a phenylene sulfone unit, a phenylene sulfide ketone unit, a phenylene sulfide ether unit, a diphenylene sulfide unit, a phenylene sulfide unit containing a substituent, a phenylene sulfide unit containing a branched structure, or the like, as its constituent units. Among these, those containing 70 mol % or more, particularly 90 mol % or more of p-phenylene sulfide units are preferred, and poly(p-phenylene sulfide) is more preferred.

[0010] The polyarylene sulfide resin used as component A of the present invention preferably has a polydispersity (Mw / Mn) expressed by the weight average molecular weight (Mw) and the number average molecular weight (Mn) of 2.7 or more, more preferably 2.8 or more, and even more preferably 2.9 or more. If the polydispersity is less than 2.7, there may be a large amount of burrs generated during molding. The upper limit of the polydispersity (Mw / Mn) is not particularly specified, but it is preferably 10 or less. Here, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values ​​calculated in terms of polystyrene by gel permeation chromatography (GPC). 1-chloronaphthalene was used as the solvent, and the column temperature was set to 210°C.

[0011] The method for producing the polyarylene sulfide resin is not particularly limited, and the resin is polymerized by a known method. For example, the methods described in U.S. Patent Nos. 4,746,758 and 4,786,713, JP-A-2013-522385, JP-A-2012-233210, and JP-A-5167276 are included. These methods involve directly heating a diiodoaryl compound and solid sulfur without a polar solvent to polymerize them.

[0012] The method includes an iodization step and a polymerization step. In the iodization step, an aryl compound is reacted with iodine to obtain a diiodoaryl compound. In the subsequent polymerization step, the diiodoaryl compound is polymerized with solid sulfur using a polymerization terminator to produce a polyarylene sulfide resin. Iodine is generated in gas form in this step, which is recovered and reused in the iodization step. Iodine is essentially a catalyst.

[0013] A representative example of solid sulfur used in the above-mentioned preparation method is cyclooctasulfur (S8) in which eight atoms are bonded at room temperature. However, the sulfur compound used in the polymerization reaction is not limited, and any form that is solid or liquid at room temperature can be used.

[0014] Representative diiodoaryl compounds used in the above-mentioned production method include at least one selected from the group consisting of diiodobenzene, diiodonaphthalene, diiodobiphenyl, diiodobisphenol, and diiodobenzophenone. Also, derivatives of iodoaryl compounds to which an alkyl group or a sulfone group is bonded, or to which oxygen or nitrogen is introduced, are used. Iodoaryl compounds are classified into different isomers depending on the bonding position of the iodine atom, and preferred examples of these isomers are compounds in which iodine is symmetrically located at both ends of the molecule of the aryl compound, such as p-diiodobenzene, 2,6-diiodonaphthalene, and p,p'-diiodobiphenyl. The content of the iodoaryl compound is preferably 500 to 10,000 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.

[0015] Representative polymerization terminators that can be used in the above-mentioned production method include monoiodoaryl compounds, benzothiazoles, benzothiazole sulfenamides, thiurams, dithiocarbamates, and the like. Examples of the monoiodoaryl compounds include at least one selected from the group consisting of iodobiphenyl, iodophenol, iodoaniline, and iodobenzophenone. Examples of the benzothiazoles include at least one selected from the group consisting of 2-mercaptobenzothiazole and 2,2'-dithiobisbenzothiazole. Examples of the benzothiazole sulfenamides include at least one selected from the group consisting of N-cyclohexylbenzothiazole 2-sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, 2-morpholinothiobenzothiazole, benzothiazole sulfenamide, dibenzothiazole disulfide, and N-dicyclohexylbenzothiazole 2-sulfenamide. Examples of the thiurams include at least one selected from the group consisting of tetramethylthiuram monosulfide and tetramethylthiuram disulfide. A preferred example of the dithiocarbamates is at least one selected from the group consisting of zinc dimethyldithiocarbamate and zinc diethyldithiocarbamate. A preferred example of the aromatic sulfide compound is at least one selected from the group consisting of diphenyl sulfide, diphenyl disulfide, diphenyl ether, biphenyl, and benzophenone. In addition, in any of the polymerization terminators, one or more functional groups may be substituted on the conjugated aromatic ring skeleton. Examples of the functional group include a hydroxy group, a carboxy group, a mercapto group, an amino group, a cyano group, a sulfo group, and a nitro group, and preferred examples include a carboxy group and an amino group, and more preferred examples include a functional group having a peak at 1600 to 1800 cm in the FT-IR spectrum. -1 or 3300~3500cm -1 The content of the polymerization terminator is preferably 1 to 30 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined taking into consideration the formation of disulfide bonds.

[0016] In the above-mentioned production method, a polymerization catalyst may be used, and a representative example of the polymerization catalyst is a nitrobenzene-based catalyst. A preferred example of the nitrobenzene-based catalyst is at least one selected from the group consisting of 1,3-diiodo-4-nitrobenzene, 1-iodo-4-nitrobenzene, 2,6-diiodo-4-nitrophenol, iodonitrobenzene, and 2,6-diiodo-4-nitroamine. The content of the polymerization catalyst is preferably 0.01 to 20 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.

[0017] By using this polymerization method, it is possible to obtain a polyphenylene sulfide resin having excellent cost performance without the need to substantially reduce the chlorine content and the sodium content.

[0018] The polyphenylene sulfide resin of the present invention may also contain polyphenylene sulfide resins obtained by other polymerization methods.

[0019] (B component: graphite) The graphite used as the B component of the present invention may be any graphite that is generally called graphite. The type of graphite is not particularly limited, such as scaly graphite, flake graphite, expanded graphite, and artificial graphite. However, from the viewpoint of thermal conductivity, expanded graphite that has been thermally expanded is particularly preferred. Expanded graphite is generally obtained by heat-treating natural graphite, petroleum coke, petroleum pitch, amorphous carbon, etc., which is naturally produced as a mineral, at 2000°C or higher to artificially orient irregularly arranged fine graphite crystals, immersing the artificial graphite in concentrated sulfuric acid, concentrated nitric acid, etc., and further treating it with an oxidizing agent such as hydrogen peroxide or hydrochloric acid to generate a graphite intercalation compound, and then washing with water and rapidly heating at 800 to 1000°C to expand the graphite in the C-axis direction of the raw graphite, but the heat treatment temperature, acid treatment components, etc. are not particularly limited. The particle size of the graphite is preferably 1 to 1000 μm, more preferably 10 to 500 μm. If the particle size is less than 1 μm, the thermal conductivity may be poor, and if it exceeds 1000 μm, the appearance of the molded product may be poor.

[0020] The surface of the graphite in the present invention may be subjected to a surface treatment in order to increase the affinity with the polyarylene sulfide resin, as long as the properties of the composition of the present invention are not impaired. Furthermore, a mixture of two or more types of graphite may be used.

[0021] The content of component B is 5 to 50 parts by weight, preferably 10 to 40 parts by weight, and more preferably 20 to 30 parts by weight, relative to 100 parts by weight of component A. If the content of component B is less than 5 parts by weight, sufficient thermal conductivity cannot be obtained, and if it exceeds 50 parts by weight, production processability is poor.

[0022] (Component C: Talc) Talc has the chemical formula Mg3Si4O 10 It is a type of mineral represented by the formula (OH)2. Any talc generally known as talc can be used as the talc used as component C of the present invention, and is not limited by the type or amount of impurities or the place of origin. Furthermore, the surface of the talc in the present invention may be subjected to a surface treatment such as an epoxy-based, amino-based, silane-based, or fatty acid-based treatment in order to increase the affinity with the polyarylene sulfide resin, as long as the properties of the composition of the present invention are not impaired. Furthermore, a mixture of two or more types of talc may be used.

[0023] The particle size of the talc is less than 10 μm, preferably 0.5 to 8 μm, and more preferably 1 to 7 μm. If the particle size is 10 μm or more, the electrical insulation properties are poor. The particle size was measured by a laser diffraction / scattering method using HRA9320-X100 (manufactured by Microtrac).

[0024] The content of component C is 5 to 80 parts by weight, preferably 10 to 60 parts by weight, and more preferably 20 to 40 parts by weight, relative to 100 parts by weight of component A. If the content of component C is less than 5 parts by weight, the thermal conductivity and electrical insulation are poor, and if it exceeds 80 parts by weight, the production processability is poor.

[0025] (D component: glass fiber) The glass fiber used as component D of the present invention may be any glass fiber generally called glass fiber. The glass composition such as A glass, C glass, E glass, etc. is not particularly limited, and may contain TiO2, SO3, P2O5, etc., depending on the case. However, E glass (alkali-free glass) is more preferable when it is mixed with polyarylene sulfide resin. The glass fiber is formed by quenching molten glass while stretching it by various methods to form a predetermined fiber shape. The quenching and stretching conditions in such a case are not particularly limited. In addition, the cross-sectional shape may be a perfect circle, or a shape other than a perfect circle such as an ellipse, a cocoon, or a three-lobe shape. Furthermore, a mixture of a perfect circle glass fiber and a shape other than a perfect circle glass fiber may be used. The glass fiber may be coated or bundled with a resin such as an ethylene / vinyl acetate copolymer, polyurethane, or epoxy resin.

[0026] The content of component D is 5 to 80 parts by weight, preferably 10 to 70 parts by weight, and more preferably 20 to 60 parts by weight, per 100 parts by weight of component A. If the content is less than 5 parts by weight, sufficient strength cannot be obtained, and if it exceeds 80 parts by weight, production processability is poor.

[0027] The resin composition of the present invention may further contain a non-fibrous filler other than components B and C, as long as the effect of the present invention is not impaired. The non-fibrous filler is not particularly limited, but may be sericite, kaolin, mica, clay, bentonite, asbestos, silicates such as alumina silicate, swellable layered silicates such as montmorillonite and synthetic mica, alumina, acid Examples of the inorganic fillers include metal compounds such as silicon oxide, magnesium oxide, zirconium oxide, titanium oxide, and iron oxide; carbonates such as calcium carbonate, magnesium carbonate, and dolomite; sulfates such as calcium sulfate and barium sulfate; glass beads, ceramic beads, boron nitride, calcium phosphate, and silica.

[0028] The resin composition of the present invention may contain an elastomer component within a range that does not impair the effects of the present invention. Suitable elastomer components include core-shell graft copolymer resins such as acrylonitrile-butadiene-styrene copolymers (ABS resins), methyl methacrylate-butadiene-styrene copolymers (MBS resins), and silicone-acrylic composite rubber graft copolymers, or thermoplastic elastomers such as silicone thermoplastic elastomers, olefin thermoplastic elastomers, polyamide thermoplastic elastomers, polyester thermoplastic elastomers, and polyurethane thermoplastic elastomers.

[0029] The resin composition of the present invention may contain, within the scope of the effect of the present invention, antioxidants and heat resistance stabilizers (hindered phenols, hydroquinones, phosphites, and their substituted derivatives, etc.), weathering agents (resorcinols, salicylates, benzotriazoles, benzophenones, hindered amines, etc.), release agents and lubricants (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, various bisamides, bisureas, polyethylene wax, etc.), pigments (cadmium sulfide, fluorine, etc.), and the like. Other additives may include phthalocyanine, carbon black, etc., dyes (nigrosine, etc.), crystal nucleating agents, plasticizers (octyl p-oxybenzoate, N-butylbenzenesulfonamide, etc.), flame retardants (red phosphorus, phosphate esters, melamine cyanurate, hydroxides such as magnesium hydroxide and aluminum hydroxide, ammonium polyphosphate, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, brominated epoxy resin, or combinations of these brominated flame retardants with antimony trioxide, etc.), and other polymers.

[0030] (Production of resin composition) The resin composition of the present invention can be produced by mixing the above-mentioned components simultaneously or in any order using a mixer such as a tumbler, V-type blender, Nauter mixer, Banbury mixer, kneading roll, or extruder. Melt kneading using a twin-screw extruder is preferred, and if necessary, any component is preferably fed into the other melt-mixed components from a second feed port using a side feeder or the like. The resin extruded as described above is directly cut and pelletized, or is pelletized by cutting the strands with a pelletizer after forming them. When it is necessary to reduce the influence of external dust during pelletization, it is preferred to purify the atmosphere around the extruder. The shape of the obtained pellets can be a general shape such as a cylinder, a rectangular column, or a sphere, but is more preferably a cylinder. The diameter of such a cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and even more preferably 2 to 3.5 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and even more preferably 2.5 to 4 mm.

[0031] (About molded products) Molded articles made of the resin composition of the present invention can be obtained by molding the pellets produced as described above. Preferably, they are obtained by injection molding or extrusion molding. Injection molding includes not only ordinary molding methods, but also injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including a method of injecting a supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, multi-color molding, sandwich molding, and ultra-high speed injection molding. Molding can be performed using either a cold runner method or a hot runner method. In addition, extrusion molding can produce various extrusion molded products, sheets, films, and the like. Sheets and films can also be molded using an inflation method, a calendar method, a casting method, and the like. Furthermore, it is possible to mold the resin composition of the present invention into a heat-shrinkable tube by applying a specific stretching operation. It is also possible to mold the resin composition of the present invention into a molded article by rotational molding, blow molding, and the like. Effect of the Invention

[0032] The resin composition of the present invention has excellent strength while exhibiting excellent thermal conductivity and electrical insulation, and is therefore suitable for use in a wide range of electronic components, including sensors, LED lamps, connectors, small switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, semiconductors, liquid crystal displays, FDD carriages, FDD chassis, hard disk drive parts (hard disk drive hubs, actuators, hard disk substrates, etc.), DVD parts (optical pickups, etc.), motor brush holders, parabolic antennas, and computer-related parts; VTR parts, television parts, irons, hair irons, etc. The products can be used in a variety of applications, including home and office electrical appliance parts such as hair dryers, rice cooker parts, microwave oven parts, audio parts, audio equipment parts such as laser discs (registered trademark) and compact discs, lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, etc.; machine-related parts such as office computer-related parts, telephone-related parts, facsimile-related parts, copier-related parts, cleaning jigs, motor parts, lighters, typewriters, etc.; optical equipment and precision machinery-related parts such as microscopes, binoculars, cameras, clocks, etc.; and vehicle parts such as lamp reflectors, lamp housings, center console panels, deflector parts, car navigation parts, and auto mobile computer parts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present inventors currently consider the best embodiment of the present invention to be one that embodies the preferred ranges of each of the above-mentioned requirements, and representative examples thereof are described in the following examples, although the present invention is not limited to these embodiments. EXAMPLES

[0034] [Evaluation of resin composition] (1) Tensile breaking strength Measured in accordance with ISO527 (measurement condition: 23°C). The test pieces were molded by the following method. A larger value of this indicates better strength of the resin composition. (2) Thermal conductivity A square plate (50 mm × 100 mm × 4 mm t) was molded under the following conditions, and the thermal conductivity in the flow direction of the sample was measured by the laser flash method. A larger value of this indicates better thermal conductivity of the resin composition. (3) Electrical insulation A square plate (150 mm × 150 mm × 3 mm t) was molded under the following conditions, and a 50 mm × 50 mm × 3 mm t portion at the center was cut out. For the cut-out square plate, the volume resistivity was measured using a super insulation meter (manufactured by HIOKI).

[0035] [Examples 1 - 8, Comparative Examples 1 - 7] A polyarylene sulfide resin, graphite, talc, and glass fiber were melt-kneaded in the respective compounding amounts shown in Table 1 using a vented twin-screw extruder to obtain pellets. The vented twin-screw extruder used was TEX30α-38 (fully meshing, co-rotating) manufactured by Nippon Steel Works, Ltd. The extrusion conditions were a discharge rate of 20 kg / h, a screw rotation speed of 200 rpm, a vent vacuum degree of 3 kPa, and the extrusion temperature was 320°C from the first feed port to the die part. The glass fiber and graphite were supplied from the second feed port using the side feeder of the above extruder, and the polyarylene sulfide resin and talc were supplied to the extruder from the first feed port. Here, the first feed port refers to the feed port farthest from the die, and the second feed port refers to the feed port located between the die and the first feed port of the extruder. The obtained pellets were dried in a hot air circulation dryer at 130°C for 6 hours, and then test pieces for evaluation were molded using an injection molding machine (EC160NII-4Y manufactured by Toshiba Machine Co., Ltd.) at a cylinder temperature of 320°C and a mold temperature of 140°C.

[0036] Each component denoted by the symbol notation in Table 1 is as follows. <Component A> A-1: A polyphenylene sulfide resin obtained by the following production method [Production method] 300.00 g of paradibenzene and 27.00 g of sulfur were charged with 0.60 g of diphenyldisulfide (content of 0.65% by weight based on the weight of the finally polymerized polyphenylene sulfide resin) as a polymerization terminator, heated to 180 °C to completely melt and mix them, then the temperature was raised to 220 °C, and the pressure was reduced to 200 Torr. The obtained mixture was subjected to a polymerization reaction for 8 hours while gradually changing the temperature and pressure so that the final temperature and pressure were 320 °C and 1 Torr, respectively, to produce a polyphenylene sulfide resin. The dispersity (Mw / Mn) represented by the weight average molecular weight (Mw) and the number average molecular weight (Mn) was 4.3.

[0037] <Component B> B-1: Expanded graphite (E-40 manufactured by Nishimura Graphite Co., Ltd., average particle size: 250 μm) <Component C> C-1: Talc (ultra-5L manufactured by IMI FABI, average particle size: 2 μm) C-2: Talc (Victorylite TK-RC manufactured by Kosei Yamakyo Co., Ltd., average particle size: 5 μm) C-3: Talc (Victorylite SG-A manufactured by Kosei Yamakyo Co., Ltd., average particle size: 20 μm) <Component D> D-1: Chopped glass fiber with circular cross-section (T-732H manufactured by Nippon Electric Glass Co., Ltd., diameter: 10.5 μm, cut length: 3 mm, urethane-epoxy-based sizing agent)

[0038]

Table 1

Claims

1. The resin composition contains 100 parts by weight of (A) polyarylene sulfide resin (component A), 5 to 50 parts by weight of (B) thermally expanded graphite (component B), 5 to 80 parts by weight of (C) talc (component C), and 5 to 80 parts by weight of (D) glass fiber (component D), wherein the particle size of component C measured by laser diffraction method is less than 10 μm.

2. A molded article made of the resin composition according to claim 1.

3. A method for producing a resin composition comprising 100 parts by weight of (A) polyarylene sulfide resin (component A), 5 to 50 parts by weight of (B) thermally expanded graphite (component B), 5 to 80 parts by weight of (C) talc (component C), and 5 to 80 parts by weight of (D) glass fiber (component D), wherein the particle size of component C measured by laser diffraction method is less than 10 μm.

Citation Information

Patent Citations

  • Highly heat conductive resin composition

    JP2002256147A

  • High heat radiation polyarylene sulfide resin composition and molded product

    JP2013075996A

  • Polyphenylene sulfide resin composition and molded article

    JP2016088984A

  • Rein pellet, method for producing resin pellet, molded body and method for producing molded body

    JP2020079412A